2012
DOI: 10.1103/physrevb.86.165306
|View full text |Cite
|
Sign up to set email alerts
|

Optical control of the spin state of two Mn atoms in a quantum dot

Abstract: We report on the optical spectroscopy of the spin of two magnetic atoms (Mn) embedded in an individual quantum dot interacting with a single electron, a single exciton, or a single trion. As a result of their interaction to a common entity, the Mn spins become correlated. The dynamics of this process is probed by time-resolved spectroscopy, which permits us to determine an optical orientation time in the range of a few tens of nanoseconds. In addition, we show that the energy of the collective spin states of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
(89 reference statements)
1
32
0
Order By: Relevance
“…Semiconductor quantum dots (QDs) permit efficient electrical or optical manipulation of individual carrier spins [6][7][8][9] . It has been shown that the optical properties of a QD can also be used to control the spin state of individual [10][11][12][13][14][15] or pairs 16,17 of magnetic atoms. The spin of a magnetic atom in a QD can be prepared by the injection of spin polarized carriers and its state can be read through the energy and polarization of the photons emitted by the QD [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor quantum dots (QDs) permit efficient electrical or optical manipulation of individual carrier spins [6][7][8][9] . It has been shown that the optical properties of a QD can also be used to control the spin state of individual [10][11][12][13][14][15] or pairs 16,17 of magnetic atoms. The spin of a magnetic atom in a QD can be prepared by the injection of spin polarized carriers and its state can be read through the energy and polarization of the photons emitted by the QD [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…The Autler-Townes effect in the fine structure of a neutral or charged QD [9,10], the Mollow absorption spectrum of an individual QD [11] and the emission of an optically dressed exciton and biexciton complex [12] have been reported. Exploiting these optical properties of QDs, it has been demonstrated during the last years the possibility to optically probe and control the spin of individual or pairs of Manganese (Mn) atoms both in II-VI [13,14] and III-V [15][16][17] DMS. Recently, other magnetic elements, like Co, have also been successfully incorporated in II-VI semiconductor QDs [18].…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor quantum dots (QDs) doped by a single or few magnetic impurities have been studied in the last decade in order to investigate the exchange interaction between spin carriers in the quantum regime 1-9 , and the potential of such system as a solid-state quantum bit [10][11][12][13][14][15][16][17][18][19] . In such QDs the dominant 2-spin interaction is the exchange interaction between the magnetic dopant and the QD-confined hole (up to a few meV).…”
Section: Introductionmentioning
confidence: 99%